ResearchProgressonThermalErrorCompensationandStructuralOptimizationofHigh-SpeedMotorizedSpindle - LI Zhao long; ZHU Wen ming (Journal of Harbin University of Science and Technology)
Thermal displacement control of motorized spindles is one of the key problems in the machining process. Control thermal displacement of the motorized spindle to improve machining accuracy and surface quality. One of the common methods is to reduce the temperature of the motorized spindle by the cooling system and introduce a cooling medium such as water or oil inside or outside. Optimizing the design and control strategy of the cooling system can further improve the control effect of thermal displacement. Another method is to control the thermal displacement of the motorized spindle through thermal compensation. The temperature sensor is installed and combined with the pre-established thermal compensation model to compensate and adjust the position of the tool or workpiece in real time to realize high-precision machining. At the same time, choosing materials with good thermal stability is another strategy to control thermal displacement. They have a low thermal expansion coefficient and high thermal conductivity, which can reduce the displacement effect caused by thermal deformation. To sum up, the thermal displacement control of motorized spindles comprehensively considers the cooling system, thermal compensation, and materials, and reasonable application of these methods can effectively reduce the thermal displacement of motorized spindles and improve the machining accuracy and surface quality.